Attention to Emotional Information Is Associated With Cytokine Responses to Psychological Stress - Viktoriya Maydych (Frontiers in Neuroscience, 2018)
This study aimed to investigate the impact of mental stress on salivary cytokines and attention to emotional stimuli, as well as associations between stress-induced changes of immune and cognitive parameters. In a randomized order a total of 60 young adults were assigned to one of two stress conditions with varying stress intensity. High stress was induced by a socially evaluated Paced Auditory Serial Addition Test (PASAT). As a low stress task a paper-and-pencil version of PASAT was administered. Salivary cytokines were measured before, 5 min after, and 45 min after completion of the stress task, and were assayed for pro- and anti-inflammatory cytokines. Three distinct types of attention – alerting, orienting, and executive control – were measured by the modified Emotional Attention Network Test Integration (E-ANTI). IL-1β and IL-6 increased only in the high-stress group. Significant increases in IFN-α, IFN-γ, TNF-α, and IL-10 at 45 min after stress induction (all p’s < 0.05) were observed in both the high-stress and the low-stress group. Alerting attention was positively related to more pronounced increases in IFN-α and TNF-α in both groups. Further, better orienting attention after presentation of negative cues was associated with higher increases in IFN-α, TNF-α, IL-2, IL-5, and IL-10 in both groups, and higher overall levels of IFN-α, IFN-γ, and IL-12p70 in the high-stress group. There were no systematic gender differences in cytokine responses. We conclude that attention processes modulate the increases of salivary cytokines after stress exposure, and that these effects depend on stress level, particular attention network, and stimulus valence.